Optimalisasi Environment Learning Melalui Etnobiologi Dalam Kerangka Ekonomi Biru untuk Meningkatkan Literasi Ekologi di Sekolah Pesisir Kalimantan Barat - Novi Nurmayanti; Dini Lestary (LPPM Institut Pendidikan Nusantara Global, 2026)
Environmental degradation and the declining ecological awareness of younger generations highlight the need for contextual environmental learning in coastal schools. This study aimed to develop and evaluate an Environment Learning model integrating ethnobiology within the Blue Economy framework to improve ecological literacy among students in coastal areas of West Kalimantan. The research employed a Research and Development (R&D) approach using mixed methods. Qualitative data were collected through observations, interviews, and Focus Group Discussions (FGDs) to identify local ethnobiological knowledge, while quantitative data were obtained using ecological literacy tests administered before and after the implementation of the developed learning model. Data were analyzed using descriptive statistics, an independent sample t-test, and effect size analysis. The findings demonstrated that students who learned using the developed module achieved a significantly higher mean ecological literacy score (83) than those receiving conventional instruction (53) (p < 0.05). The greatest improvements were observed in sustainability actions, ecological awareness, understanding of environmental interactions, and collaborative skills. The novelty of this study lies in integrating local ethnobiological knowledge with the Blue Economy framework into a contextual environmental learning model, providing an innovative approach to strengthening ecological literacy while promoting sustainable coastal resource management. The developed model offers practical implications for environmental education and supports the integration of local wisdom into sustainable learning practices in coastal schools.